2013
DOI: 10.1111/jep.12076
|View full text |Cite
|
Sign up to set email alerts
|

The good, the bad and the early adopters: providers' attitudes about a common, commercial EHR

Abstract: PCPs practicing in settings with considerable experience using a common commercial EHR identified many positive effects, as well as two key areas for improvement - patient centredness and intelligent decision support. Providers with a propensity to adopt new technologies have more favourable perceptions of the EHR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 19 publications
2
27
0
Order By: Relevance
“…An EMR could be redesigned to merge the benefits of patient involvement and the information necessary for practicing clinical medicine (37). Our data are consistent with similar studies demonstrating the importance of patient-centered principles in redesigning EMR formats (23,24). However, the optimal mode of redesigning the EMR remains to be seen.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…An EMR could be redesigned to merge the benefits of patient involvement and the information necessary for practicing clinical medicine (37). Our data are consistent with similar studies demonstrating the importance of patient-centered principles in redesigning EMR formats (23,24). However, the optimal mode of redesigning the EMR remains to be seen.…”
Section: Discussionsupporting
confidence: 92%
“…Similarly, physicians may value a place for documentation of special considerations due to the movement toward more patient-centered medicine (23,24). …”
Section: Background and Significancementioning
confidence: 99%
“…Recent studies examining patient-centered communication have focused on eye contact and mutual gaze [20-21]. Researchers have found that the use of computers during healthcare visits negatively impacts doctor-patient communication, including decreased eye contact [22], and taking a physician's attention away from the patient in the form of gaze and body positioning [23,24]. …”
Section: Introductionmentioning
confidence: 99%
“…13 Difficulty associated with the usability of EHRs remains an important source of professional dissatisfaction; early adopters report the technology can at times interfere with communication during visits and patient-clinician eye contact. 13,15 Evidence suggests some physicians using EHRs may also engage patients in fewer physician-initiated gaze patterns (signaling a lack of attention toward the patient), and that EHR use may contribute to a sense of separation among some patients when the EHR monitor is kept away from the patient's view. 16,17 In response to concerns like these, a recently published primary care consensus statement concluded that many EHR systems need marked refinement to promote greater patient engagement.…”
mentioning
confidence: 99%